Pemahaman Konsep Pada Materi Reaksi Redoks dengan Four-Tier Test - Rahmiati Rahmiati; Ratna Kartika Irawati; Trining Puji Astutik (Tadris Biologi, Tadris Fisika and Tadris Kimia, Universitas Islam Negeri Antasari, 2022)
This study aims to determine the understanding of the redox reaction material concept of each subconcept in class X students of MAN 3 Hulu Sungai Selatan. The type of research used is descriptive statistics with a quantitative approach. The population of this study was students of class X MAN 3 Hulu Sungai Selatan with samples of class X MIA 1 and 2 totaling 63 people. Sampling technique used is Purposive Sampling. Data collection techniques were carried out using a four-tier diagnostic test. The results showed that the understanding of the concept of redox material with an average of 31.25% with moderate criteria. Understand the concept of redox reactions based on the binding and release of oxygen by 42.06%, redox reactions based on the attachment and loss of electrons by 26.98%, redox reactions based on increasing and decreasing oxidation numbers by 25.40%, determining the oxidation number of 58, 73%, oxidation-reduction reactions of 26.98%, oxidizing and reducing agents of 24.34%, and the application of redox reactions of 14.29%. Understanding the biggest concept is in the sub-concept of determining the oxidation number.